Islamic Philosophy and Ethics of Education: Al- Zarnūjī’s Concept of Taʻẓīm in his Ta‘līm al-Muta‘allim - Miftachul Huda (Universitas Islam Negeri Mataram, 2021)
Respect has demonstrated psychological, social and academic benefits; however, it has been a lack from attention for most researchers in promoting character development for the student. This article aims to critically explore respect as a moral concept and explain how respect can contribute to current discussions in developing character education, mainly from the perspective of one of the classical Muslim scholar, al-Zarnūjī, based on his esteem work on the concept of Ta‘līm al-Muta‘allim, as one of the references in learning and teaching guidelines among Islamic boarding school (pesantren) in Indonesia. Critical review from referred journal and book was conducted to the contributions in the domain of character education. There are three main discussions as the result of this study. First, it is respect to the knowledge as a light of understanding. Second, it is respect to the teacher as the most role model and actor of knowledge sharing; and third it is respect to the colleague as partner in learning process. Thus, respect in its three dimensional aspects should govern the learning and teaching process.